2023
DOI: 10.3329/bjsir.v58i1.63634
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, structural and optical properties of Gd-doped ZnO powder synthesized by solid-state reaction method

Abstract: We explored the impact of Gd doping on the structural, electronic and optical characteristics of the ZnO powder. The Gd-doped ZnO (0, 2% and 5%) powder samples have been synthesized using the conventional solid-state reaction process with varied Gd concentrations. The XRD pattern confirmed that all the studied samples are in the hexagonal wurtzite crystalline structure. The morphology has been explored using SEM images, which exhibited an agglomerated rod-like particle structure. The XPS results indicate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…On the basis of application, several methods have been adopted for sample synthesis. The sample synthesized by solid-state reaction shows decreasing band gap of ZnO with increasing Gd concentration [27]. Yayapao et al demonstrated that Gd-ZnO samples synthesized via the sonochemical method show better photocatalytic activity than undoped ZnO [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of application, several methods have been adopted for sample synthesis. The sample synthesized by solid-state reaction shows decreasing band gap of ZnO with increasing Gd concentration [27]. Yayapao et al demonstrated that Gd-ZnO samples synthesized via the sonochemical method show better photocatalytic activity than undoped ZnO [28].…”
Section: Introductionmentioning
confidence: 99%